Element of Politeness in Intercultural Communication: The Case Study of Japanese and Malaysian Tourists - Roslina, Mamat; Roswati, Abdul Rashid; Rokiah, Paee (Department of East Asian Studies, University of Malaya, Malaysia, 2021)
The number of Japanese tourists visiting Malaysia has consistently ranked in the top ten over the last 20 years. Japan has been the country of choice for Malaysian tourists over the previous ten years. It is, therefore, crucial that tourism communication in the cross-cultural context between Malaysia and Japan is used as a reference to improve the cross-cultural communication skills of the tourism employees involved. This article discusses the external structure of Japanese conversation between native Japanese speakers and Malaysian tourist guides and native Malay speakers with Japanese tourist guides. This study is qualitative and uses the discourse analysis approach. A total of four conversation sessions in the form of Free Independent Travel (FIT) tourism were held in Malacca and Tokyo. The conversations were recorded, and the researchers also made notes throughout the conversation to see the sentence structures and non-linguistic elements to complete the data. The recording was then transcribed and encoded before being analysed. Only the conversations by tourist guides were analysed and included in the contents of this article as the focus of the study is more on the external form and politeness of the Japanese language used by Malaysian and Japanese tourist guides in demonstrating solidarity and similarities in the context of cross-cultural conversation. Data analysis shows many similarities in the selection of vocabulary and specific verb forms by Japanese and Malaysian tourist guides to show courtesy and friendliness in the conversation. This proves that Japanese language skills by Malaysian tourist guides are almost on par with Japanese tourist guides. Malaysian tourist guides also have a vast knowledge of the culture and nature of the Japanese language.